An improved EGR system concept for diesel engines towards fuel neutral emissions. (5th May 2006) - Ivaldi, D.; Lisbona, M.G.; Tonetti, M.
After the fulfilment of Euro 4 emission limits, the diesel technical community now addressing the new target of 'fuel neutral emissions'. The focus is on how to reduce NOx, since the DPF has proved to be very efficient at reducing particulates. A long-term solution will be the HCCI combustion mode, but, in the mid-term, the combined use of an early premixed combustion, in a limited engine operation area, and the extensive use of conventional combustion, with extensive use of cooled EGR, could be a solution up to the medium vehicle inertia class. The paper discusses the potential of the long route (LR) EGR system. Fluid dynamics simulation results are reported and the advantages and disadvantages of this system are identified. Preliminary experimental results on engines in steady state conditions are shown and confirm the promise of the LR system.